The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1055/s-0043-122227
|View full text |Cite
|
Sign up to set email alerts
|

Initial experience with percutaneous endoscopic gastrostomy with T-fastener fixation in pediatric patients

Abstract: Background and study aims  Insertion of a percutaneous endoscopic gastrostomy (PEG) with push-through technique and T-fastener fixation (PEG-T) has recently been introduced in pediatric patients. The T-fasteners allow a primary insertion of a balloon gastrostomy. Due to limited data on the results of this technique in children, we have investigated peri- and postoperative outcomes after implementation of PEG-T in our department. Patients and methods  This retrospective chart review included all patients below … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 17 publications
(40 reference statements)
4
28
1
Order By: Relevance
“…Various methods have been proposed to prevent tube dislodgment; these include sophisticated tube designs such as low profile "button-type" tubes [128,129]. In a recent RCT, balloon-tube dislodgment was significantly less frequent in a group of patients who underwent weekly measurement of the water volume within the balloon followed by tube replacement at 3-monthly intervals [130].…”
Section: Tube Dislodgmentmentioning
confidence: 99%
“…Various methods have been proposed to prevent tube dislodgment; these include sophisticated tube designs such as low profile "button-type" tubes [128,129]. In a recent RCT, balloon-tube dislodgment was significantly less frequent in a group of patients who underwent weekly measurement of the water volume within the balloon followed by tube replacement at 3-monthly intervals [130].…”
Section: Tube Dislodgmentmentioning
confidence: 99%
“…The frequency of T‐fastener–related complications in their report was much higher than in the present study. In their report, the suture locks were removed later at 3 to 4 weeks postoperatively, compared to 1 to 2 weeks in our patients 11 . Livingston et al changed from cutting the T‐fastener sutures 3 to 4 weeks postoperatively to 5 days after LAPEG in pediatric patients.…”
Section: Discussionmentioning
confidence: 59%
“…There have been some reports regarding T‐fastener migration 10‐12 . Kvello et al reported the outcomes of PEG with T‐fastener gastropexy in 92 pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations